Biofuel Powering of Internal Combustion Engines: Production Routes, Effect on Performance and CFD Modeling of Combustion - Costa, Michela; Piazzullo, Daniele (Frontiers in Mechanical Engineering, 2018)
The use of liquid or gaseous biofuels in reciprocating internal combustion engines (ICEs) is today a relevant issue as these systems are largely diffused for both steady power generation and transportation due to their flexibility and easiness of use. The improvement and perfect control of the combustion process under non-conventional fuelling is mandatory to achieve high-energy efficiency without substantial changes to the architecture or the fuel supply system. In this perspective, the detailed characterization of multiphase reacting systems achievable though computational fluid dynamics (CFD) may give a decisive contribution. However, the assessed combustion models used for fossil fuels (diesel oil, gasoline, methane), tuned on the ground of a massive amount of experimental data, often results poor in predicting the actual behaviour of renewable fuels whose composition and properties may change also according to technology for their production. Present work aims at filling some existing gaps in biofuel combustion modeling by performing investigations on two representative engine cases, for their characterization and performance enhancement. Two approaches are followed, namely through reduced chemical kinetics coupled with turbulence within a coherent flame schematization, and through a turbulent species transport approach with detailed kinetics. Simulations are first carried out on a compression ignition (CI) ICE. The formulation of a 3D CFD model is described to reproduce the performance of this engine in a dual-fuel mode with premixed syngas from biomass gasification and a biodiesel pilot injection leading to self-ignition. Pollutants formation and energy efficiency are calculated as syngas amount and the biodiesel start of injection (SOI) are varied. Attention is then focused on the implementation of renewable alcohol fuels (ethanol and butanol), as these lasts are receiving large interest due to low production costs. A validated reduced kinetic mechanism for PRF-ethanol-butanol combustion performs well in multi-component oxidation conditions, as well as in neat fuel oxidation conditions, in terms of ignition delay time, laminar flame speed and HCCI combustion conditions. The paper shows that CFD, even at different level of approximation, may describe into detail the combustion process and provide important guidelines for the design of new generation ICEs fuelled by biofuels.